Private metropolis : the eclipse of local democratic governance - Judd, Dennis R.; McKenzie, Evan; Alexander, Alba (University of Minnesota Press, 2021)
"Examines the complex ecology of quasi-public and privatized institutions that mobilize and administer many of the political, administrative, and fiscal resources of today's metropolitan regions"-- Provided by publisher
Keywords: Metropolitan government -- United States.; Public-private sector cooperation -- United States.; Municipal services -- United States -- Finance.; Partenariat public-privé -- États-Unis.; POLITICAL SCIENCE -- American Government -- Local.; Metropolitan government; Municipal services -- Finance; Public-private sector cooperation; United States; Electronic book.